9α-Hydroxy-12-{[4-(4-methoxyphenyl)piperazin-1-yl]methyl}-4,8-dimethyl-3,14-dioxatricyclo[9.3.0.0(2,4)]tetradec-7-en-13-one - Moumou, Mohamed (International Union of Crystallography, 2012)
The title compound, C(26)H(36)N(2)O(5), was synthesized from 9α-hydroxyparthenolide (9α-hydroxy-4,8-dimethyl-12-methylene-3,14-dioxatricyclo[9.3.0.0(2,4)]tetradec-7-en-13-one), wich was isolated from the chloroform extract of the aerial parts of Anvillea radiata. The molecule is built up from fused five- and ten-membered rings with the methoxyphenylpiperazine group as a substituent. The ten-membered ring adopts an approximate chair–chair conformation, while the piperazine ring displays a chair conformation and the five-membered ring a flattened envelope conformation; the C(H)—C—C(H) atoms representing the flap lie out of the mean plane through the remaining four atoms by 0.343 (3) Å. The dihedral angle between the mean planes of the ten-membered ring and the lactone ring is 18.12 (14)°. An intramolecular O—H⋯N hydrogen bond occurs. The crystal structure features weak C—H⋯O interactions.